Human alpha 1-microglobulin levels in various body fluids. Issue 8 (August 1980) - Takagi, K; Kin, K; Itoh, Y; Enomoto, H; Kawai, T
Abstract : alpha 1-Microglobulin levels in serum and urine were estimated by using single radial immunodiffusion, resulting in the following mean values: umbilical cord blood serum, 40.6 mg/l; normal adult serum, 44.2 mg/l; and normal urine, 5.7 mg/24 h urine volume. Slightly higher levels of serum alpha 1-microglobulin were found in infants and the aged. Serum and urine alpha 1-microglobulin levels in patients with renal failure, however, were greatly increased, mean levels being 231.5 mg/l and 100.7 mg/24 h urine volume, respectively. Serum alpha 1-microglobulin levels in these patients correlated well with both serum creatinine and beta 2-microglobulin levels. Serum alpha 1-microglobulin level did not correlate positively with serum levels of other plasma proteins, such as alpha 1-antitrypsin, haptoglobin, complement, etc. Ouchterlony immunodiffusion also revealed the presence of alpha 1-microglobulin in synovial fluid, ascites, pleural effusion, amniotic fluid, cyst fluid, and cerebrospinal fluid. The levels of alpha 1-microglobulin in these fluids were measured by single radial immunodiffusion, except that its level in cerebrospinal fluid was measured by radioimmunoassay. Mean alpha 1-microglobulin concentration was 20.8 mg/l in synovial fluid, 28.7 mg/l in ascites, 21.5 mg/l in pleural effusion, 2.7 mg/l in amniotic fluid, 8.2 mg/l in cyst fluid, and 42.3 ng/ml in cerebrospinal fluid.